Evaluation of clinical and laboratory variables associated with anemia in pediatric patients on hemodialysis - Johnathan S. de Freitas; Paulo Sucasas Costa; Luciane Rezende Costa; Alessandra V. Naghettini (Elsevier, 2015)
Objective: To identify the occurrence of anemia in pediatric patients on hemodialysis and the association between hemoglobin levels and anemia in CKD-related variables. Methods: This was a retrospective study. Patients aged up to 18 years with chronic kidney disease undergoing hemodialysis at this service between January of 2009 and December of 2010 were selected. Clinical and laboratory data were obtained from medical records. Statistical analysis was performed with chi-squared test, Student's t-test and general estimating equations (GEE) using SPSS 20.0, assuming a significance level of 5%. Results: A total of 357 medical records depicting the monthly evolution of 29 patients were analyzed. The most common etiology for chronic kidney disease was malformations of the genitourinary tract (28%). Hemoglobin showed a mean (standard deviation) value of 9.20 (1.8) g/dL, with the occurrence of anemia in 65.3% of cases. Anemia was associated with hospitalization; antibiotic use; transfusion; use of intravenous iron hydroxide; low values of creatinine, hematocrit, and albumin; and high values of ferritin, aluminum, and equilibrated Kt/V (p < 0.05). The odds ratio for anemia with the use of intravenous iron hydroxide was 0.36 (95% CI: 0.25 to 0.89), i.e., a 2.78-fold higher chance of developing anemia without the use of this medication. Conclusions: Anemia predominated in children and adolescents with chronic kidney disease; intravenous iron hydroxide use was a protective factor. Resumo: Objetivo: Identificar a ocorrência de anemia entre pacientes pediátricos em hemodiálise e a associação entre os valores de hemoglobina e variáveis relacionadas à anemia na DRC. Métodos: Estudo retrospectivo. Selecionados pacientes até 18 anos de idade com doença renal crônica em hemodiálise no serviço entre janeiro de 2009 a dezembro de 2010. Verificados prontuários para coleta de dados clínicos e laboratoriais. Análise estatística com testes de qui-quadrado, t de Student e General Estimating Equations (GEE) em programa Statistical Package for the Social Sciences 20.0, assumindo-se nível de significância de 5%. Resultados: Analisadas 357 fichas de evolução médica mensal de 29 pacientes. A etiologia mais frequente para a doença renal crônica foram as malformações do trato genito-urinário (28%). Hemoglobina apresentou valor médio (desvio padrão) de 9,20 (1,8) g/dL, com ocorrência de anemia em 65,3% das consultas. Anemia associou-se a internação, uso de antibiótico, transfusão, uso de hidróxido de ferro endovenoso, valores baixos de creatinina, hematócrito e albumina e valores altos de ferritina, alumínio e Kt/V equilibrado (p < 0,05). A odds ratio para anemia com uso de hidróxido de ferro endovenoso foi 0,36 (95% IC 0,25-0,89), ou seja, uma chance 2,78 vezes maior de desenvolver anemia sem o uso dessa medicação. Conclusões: A anemia predominou em crianças e adolescentes com doença renal crônica, tendo como fator protetor o uso de hidróxido de ferro endovenoso. Keywords: Anemia, Adolescent, Child, Kidney dialysis, Renal failure, Palavras-chave: Anemia, Adolescente, Criança, Diálise renal, Insuficiência renal